International consensus on the most useful physical examination tests used by physiotherapists for patients with headache: A Delphi study. (June 2016) - Luedtke, K.; Boissonnault, W.; Caspersen, N.; Castien, R.; Chaibi, A.; Falla, D.; Fernández-de-las-Peñas, C.; Hall, T.; Hirsvang, J.R.; Horre, T.; Hurley, D.; Jull, G.; et al.
Abstract: Background: A wide range of physical tests have been published for use in the assessment of musculoskeletal dysfunction in patients with headache. Which tests are used depends on a physiotherapist's clinical and scientific background as there is little guidance on the most clinically useful tests. Objectives: To identify which physical examination tests international experts in physiotherapy consider the most clinically useful for the assessment of patients with headache. Design/methods: Delphi survey with pre-specified procedures based on a systematic search of the literature for physical examination tests proposed for the assessment of musculoskeletal dysfunction in patients with headache. Results: Seventeen experts completed all three rounds of the survey. Fifteen tests were included in round one with eleven additional tests suggested by the experts. Finally eleven physical examination tests were considered clinically useful: manual joint palpation, the cranio-cervical flexion test, the cervical flexion-rotation test, active range of cervical movement, head forward position, trigger point palpation, muscle tests of the shoulder girdle, passive physiological intervertebral movements, reproduction and resolution of headache symptoms, screening of the thoracic spine, and combined movement tests. Conclusions: Eleven tests are suggested as a minimum standard for the physical examination of musculoskeletal dysfunctions in patients with headache. Highlights: Survey on clinically useful physical examination tests for headache patients. 11 physical examination tests were regarded as clinically useful by 17 experts. In specific clinical situations additional tests (e.g. TMD screening) are required.